A detailed investigation on the phase transformation mechanism during electroplating of Cu (In, Ga) Se2 films on FTO-glass substrates. (1st November 2022) - Singh, Priti; Das, Sanjeev; Mallik, Archana
Highlights: An organized cyclic voltammetry study for unitary, binary, tertiary and quaternary baths for the Cu (In, Ga) Se2 system has been done. It was found that In would play a major role in the quaternary alloy deposition and deciding the final morphology. It was found that, quternary deposition took place in two layers i.e.. the first layer is CIS and then CGS leading to the quaternary phase. Abstract: In this study, an attempt has been made to acquire an in-depth understanding of the electroplating mechanism of Cu (In, Ga) Se2 quaternary thin films on FTO-glass substrates. A systematic approach starting with the study of unitary, binary, ternary, and finally quaternary deposition of the elements have been performed through cyclic voltammetry (CV). The salts used were CuCl2, H2 SeO3, InCl3 and GaCl3 for each stage of deposition with varying combinations and proportions. CVs were first done for unitary Cu, Se, In and Ga elements, then binary combinations of Cu-In, Cu-Se, Cu-Ga, In-Se, In-Ga, and Se-Ga system, ternary baths of Cu-In-Se and Cu-In-Ga, In-Se-Ga and Cu-Se-Ga systems, and finally quaternary Cu-In-Ga-Se system. An optimum deposition potential of −0.65 V was chosen from the position of cathodic peaks for all the baths. A thorough structural and elemental analysis, defect densities, type of conductivity was carried out for the as-deposited films. Single step deposition of CIGS was found to be impossible, hence Ga was attempted to incorporate in the films through a two-stack approach. From the position and intensity of the cathodic peaks and the phase analysis, plausible mechanism has been proposed for the quaternary alloy.